2017
DOI: 10.1155/2017/3531649
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ten Corticosteroids in Illegal Cosmetic Products by a Simple, Rapid, and High-Performance LC-MS/MS Method

Abstract: The aim of our present work was the development of a rapid high-performance liquid chromatography method with electrospray ionization and tandem mass spectrometry detection (LC-ESI-MS/MS) for the determination of several corticosteroids in cosmetic products. Corticosteroids are suspected to be illegally added in cosmetic preparations in order to enhance the curative effect against some skin diseases. Sample preparation step consists in a single extraction with acetonitrile followed by centrifugation and filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Steroids: 2016 LC-ESI-MS/MS method for determination of progesterone, testosterone, trenbolone acetate and zeranol [ 1148 ]; LC-MS/MS screening method for multi-class steroid hormone detection [ 1149 ]; detection of Detection and metabolic investigations of a novel designer steroid: 3-chloro-17 alpha-methyl-5 alpha-androstan-17 beta-ol in seized capsules using NMR, GC-MS and GC-MS/MS [ 1150 ]; HPLC-UV method for identification of corticosteroids in illegal cosmetics [ 1151 ]; LC-ESI-MS/MS for the simultaneous determination of six estrogens and six glucocorticoids in water [ 1152 ]; FPSE-UHPLC-MS/MS for the determination of four progestogens and six androgens [ 1153 ]; uHPLC-MS/MS for the analysis of sex hormones and corticosteroids [ 1154 ]; Stable isotope labeling - LC-ESI-MS/MS for quantitative analysis of androgenic and progestagenic steroids [ 1155 ]; LC-MS/MS method for selective and sensitive determination of estrogens [ 1156 ]; DLLME- HPLC/UV–vis for determination of estrogens [ 1157 ]; GC/EI-MS/MS and GC/CI -MS/MS analysis of anabolic steroids [ 1158 ]; MALDI-TOF-MS for the detection of steroids [ 1159 ]; PF-MEKC-UV for detection of steroids [ 1160 ]; 2017 CE and UHPLC to identify steroids [ 470 ]; LC-ESI-MS/MS for quantitative analysis of oestrogens (oestrone, oestradiol and oestriol) and androgens (testosterone and 15 alpha-testosterone) [ 1161 ]; LC-ESI-MS/MS for the determination of several corticosteroids illegally added to cosmetic products [ 1162 ]; LC-APCI-MS for determination of sterols and steroids [ 1163 ]; review of methods for isolation and characterization of brassinosteroids in plants [ 1164 ] analysis of anabolic steroids by LPPI-MS [ 1165 ]; identification of steroids in drug products using RP-HPLC-UV-detection and GC-MS [ 1166 ]; HPLC method for determination of steroids [ 1167 ]; 2018 GC-MS method to detect anabolic androgenic steroids (androsterone, nandrolene, dehydroepiandrosterone, 5a-androstane-3 beta, 17 beta-diol, dihydrotestosterone, testosterone, methenolone acetate, methandienone, boldenone and fluoxymesterone) in food supplements [ 1168 ]; differential pulse voltammetry and amperometry for steroids in commercial pharmaceutical formulations [ 1169 ]; considerations for validation of chromatographic mass spectrometric methods for the quantification of endogenous substances in forensics [ 1170 ]; availability and ease of purchase of illicit anabolic androgenic steroids and testosterone preparations on the Internet [ 1171 ]; UHPLC-MS/MS method for simultaneous determination of 12 hair-growth compounds (including steroids) in adulterated products [ 1172 ...…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…Steroids: 2016 LC-ESI-MS/MS method for determination of progesterone, testosterone, trenbolone acetate and zeranol [ 1148 ]; LC-MS/MS screening method for multi-class steroid hormone detection [ 1149 ]; detection of Detection and metabolic investigations of a novel designer steroid: 3-chloro-17 alpha-methyl-5 alpha-androstan-17 beta-ol in seized capsules using NMR, GC-MS and GC-MS/MS [ 1150 ]; HPLC-UV method for identification of corticosteroids in illegal cosmetics [ 1151 ]; LC-ESI-MS/MS for the simultaneous determination of six estrogens and six glucocorticoids in water [ 1152 ]; FPSE-UHPLC-MS/MS for the determination of four progestogens and six androgens [ 1153 ]; uHPLC-MS/MS for the analysis of sex hormones and corticosteroids [ 1154 ]; Stable isotope labeling - LC-ESI-MS/MS for quantitative analysis of androgenic and progestagenic steroids [ 1155 ]; LC-MS/MS method for selective and sensitive determination of estrogens [ 1156 ]; DLLME- HPLC/UV–vis for determination of estrogens [ 1157 ]; GC/EI-MS/MS and GC/CI -MS/MS analysis of anabolic steroids [ 1158 ]; MALDI-TOF-MS for the detection of steroids [ 1159 ]; PF-MEKC-UV for detection of steroids [ 1160 ]; 2017 CE and UHPLC to identify steroids [ 470 ]; LC-ESI-MS/MS for quantitative analysis of oestrogens (oestrone, oestradiol and oestriol) and androgens (testosterone and 15 alpha-testosterone) [ 1161 ]; LC-ESI-MS/MS for the determination of several corticosteroids illegally added to cosmetic products [ 1162 ]; LC-APCI-MS for determination of sterols and steroids [ 1163 ]; review of methods for isolation and characterization of brassinosteroids in plants [ 1164 ] analysis of anabolic steroids by LPPI-MS [ 1165 ]; identification of steroids in drug products using RP-HPLC-UV-detection and GC-MS [ 1166 ]; HPLC method for determination of steroids [ 1167 ]; 2018 GC-MS method to detect anabolic androgenic steroids (androsterone, nandrolene, dehydroepiandrosterone, 5a-androstane-3 beta, 17 beta-diol, dihydrotestosterone, testosterone, methenolone acetate, methandienone, boldenone and fluoxymesterone) in food supplements [ 1168 ]; differential pulse voltammetry and amperometry for steroids in commercial pharmaceutical formulations [ 1169 ]; considerations for validation of chromatographic mass spectrometric methods for the quantification of endogenous substances in forensics [ 1170 ]; availability and ease of purchase of illicit anabolic androgenic steroids and testosterone preparations on the Internet [ 1171 ]; UHPLC-MS/MS method for simultaneous determination of 12 hair-growth compounds (including steroids) in adulterated products [ 1172 ...…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…Literature survey revealed that (CIP) has been determined as a single component using spectrophotometry [810], thin layer chromatography [11, 12], HPLC [13, 14], capillary electrophoresis [15, 16], and chemometric method [17, 18]. Estimation of (FLU) as single formulation was accomplished using spectrophotometry [19], gas chromatography [20], thin layer chromatography [21], and HPLC [22–27].…”
Section: Introductionmentioning
confidence: 99%
“…To standardize the market and protect consumers’ legitimate rights and interests, it is necessary to establish an efficient and sensitive method for detecting DE in cosmetics. The most commonly used method of detecting DE in cosmetics is mass spectrometric analysis [5, 6], but this method is inconvenient and cannot be used for real-time high-throughput detection in the field. In China, the LOD achieved with the national standard method of detecting glucocorticoids (National Standard of the People’s Republic of China GB/T 24800.2–2009)—a method based on LC-MS-MS and TLC—was 0.03 μg/g, and the LOQ was 0.1 μg/g.…”
Section: Introductionmentioning
confidence: 99%